2020
DOI: 10.21203/rs.3.rs-27357/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk and predictors of in-hospital mortality from COVID-19 in patients with diabetes and cardiovascular disease

Abstract: Background: Diabetes mellitus (DM) and cardiovascular disease (CVD) are present in a large number of patients with novel Coronavirus disease 2019 (COVID-19). We aimed to determine the risk and predictors of in-hospital mortality from COVID-19 in patients with DM and CVD.Methods: This retrospective cohort study included hospitalized patients aged ≥ 18 years with confirmed COVID-19 in Alborz province, Iran, from 20 February 2020 to 25 March 2020. Data on demographic, clinical and outcome (in-hospital mortality)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Nevertheless, the region is home to more than 50 million elderly (aged 60 years and over) (United Nations, 2019), who can be considered at elevated risk of severe COVID-19 disease. Additionally, the continent has seen a steady increase in non-communicable diseases (NCD) such as diabetes (Ojuka and Goyaram, 2014) and hypertension (Bigna et al, 2017), which have been linked to COVID-19 severity (Rastad et al, 2020;Zhou et al, 2020). Furthermore, the continent carries a high burden of infectious diseases such as HIV and tuberculosis, which have been speculated to represent particular risk factors for severe COVID-19 disease as well (Davies, 2020).…”
Section: Covid-19 In Sub-saharan Africamentioning
confidence: 99%
“…Nevertheless, the region is home to more than 50 million elderly (aged 60 years and over) (United Nations, 2019), who can be considered at elevated risk of severe COVID-19 disease. Additionally, the continent has seen a steady increase in non-communicable diseases (NCD) such as diabetes (Ojuka and Goyaram, 2014) and hypertension (Bigna et al, 2017), which have been linked to COVID-19 severity (Rastad et al, 2020;Zhou et al, 2020). Furthermore, the continent carries a high burden of infectious diseases such as HIV and tuberculosis, which have been speculated to represent particular risk factors for severe COVID-19 disease as well (Davies, 2020).…”
Section: Covid-19 In Sub-saharan Africamentioning
confidence: 99%
“…Studies had found numerous parameters to be related with mortality in COVID-19. [8][9][10] A specific worry for COVID-19 vaccines is that a vaccine with great efficacy against COVID-19 disease (VEDIS) but low efficacy against SARS-CoV-2 infection (VESUSC), would largely convert symptomatic infections to asymptomatic infections. Furthermore, if the vaccination does not lower infectiousness (VEINF = 0), it might in theory lead to increased spread of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…The findings corroborate previous results for in-hospital mortality, which did not take into account patient discharge as a competing event. [91][92][93][94][95][96] To our knowledge, we are among the first few to consider discharge versus in-hospital mortality among COVID-19 patients under a competing risk regression framework. [57] Ignoring their competing relationship can lead to biased estimates of effects of risk factors for either event.…”
Section: Discussionmentioning
confidence: 99%